A Battle Against the Opioid Crisis: Deciphering the Molecular Control of Opioid Receptors in an Effort to Design Safer Analgesics - Mohamud, Abdulhamid (Université d'Ottawa / University of Ottawa, 2019)
Opioid receptors are central to the development of tools that can be used to manage and fight against the opioid crisis that is prevalent in North America. They are part of a large protein family called G-protein-Coupled Receptors (GPCRs), which are the most therapeutically targeted receptors within the human body. Once activated, the receptors lead to the activation of multiple different signaling pathways such the -arrestin and G-protein signaling pathways. The -Arrestin pathway is usually associated with the side effects of opioid analgesics. An allosteric site that binds to sodium was identified within the delta-opioid receptor (DOR). Previous studies have found that the sodium cavity can regulate the activation of different signaling pathways and thus act at the functional selectivity level. Our lab has identified a subset of small molecules targeting this cavity. This finding supports the druggability of this site and thus opens the door for the development of a novel pharmacological entity to control opioid receptor activities. This thesis focuses on the characterization of the sodium cavity by performing structure activity relationship (SAR) studies on the delta opioid receptor with three allosteric modulators: MIA, HMA and zoniporide. We report that, through site-directed mutagenesis and functional studies, mutations in the allosteric sodium site has an impact on the receptor functionalities including ligand recognition, efficacy and also allosterism by small molecules; however, the mutations do not prevent the binding of the allosteric modulators to the receptor. We also report the development of a novel biomedical tool that can be used to study the recruitment of the G-protein subtypes as well as the arrestin subtypes. Our data suggest it is possible to design drugs that will target the sodium pocket and this site has a major role within DOR and could be used to design novel modulators with unique pharmacological properties. My work will serve as a platform to study other members of the opioid receptor family and for the future rational design of novel modulators.
Keywords: Opioid; Pharmacology; Amiloride Derivatives; Cell Biology